Investigating the Role of Ly6G+ Neutrophils in Incisional and Inflammatory Pain by Multidimensional Pain-Related Behavioral Assessments: Bridging the Translational Gap - Segelcke, Daniel; Pradier, Bruno; Reichl, Sylvia; Schäfer, Lukas C.; Pogatzki-Zahn, Esther M. (Frontiers in Pain Research, 2021)
Within recent times, preclinical pain research has failed to develop genuinely new analgesics for clinical use. This fact is reflected by a high number of patients, limited efficacy of drugs accompanied by side effects, and long-term opioid intake. Two main aspects have been addressed that hinder translation: the use of non-relevant pain models and a mismatch between pain-related outcomes in preclinical and clinical studies. Conversely, disease-specific pain models that mirror the clinical situation more closely and multidimensional behavioral outcomes measures that objectively and reproducibly assess relevant pain-related symptoms in a preclinical setting could improve the translation. Mechanistically, one matter of debate is the role of Ly6G+ neutrophil granulocytes (NG) for pain. NG are essential to eliminate pathogens and promote wound healing. For this purpose, various pro- and anti-inflammatory mediators are released, some of which could ameliorate or enhance pain. However, the contribution of NG in different pain entities is contradictory if reflexed-based assays are used and completely unknown in the context of non-evoked and movement-evoked pain. Here, we combined withdrawal reflex-based assays with novel, video-based assessments for non-evoked (NEP) and movement-evoked (MEP) pain-related behavior in two pain models in mice. The pain models utilized here were one for incisional (INC) and one for pathogen/adjuvant-induced inflammation (CFA), translating well to postsurgical and inflammatory pain entities. Second, we have used depletion of NG and applied the battery of behavioral assessments to investigate the role of NG migration for different pain modalities. Our comprehensive behavioral approach identified pain-related behaviors in mice that resemble (NEP) or differentiate (MEP) behavioral trajectories compared to mechanical and heat hypersensitivity, thereby indicating modality-dependent mechanisms. Further, we show that injury-induced accumulation of NG minimally affects pain-related behaviors in both pain models. In conclusion, we report a novel assessment to detect NEP in mice after unilateral injuries using a more unbiased approach. Additionally, we are able to detect antalgic gait for both pain entities with unique trajectories. The different trajectories between MEP and other pain modalities suggest that the underlying mechanisms differ. We further conclude that NG play a subordinate role in pain-related behaviors in incisional and inflammation pain.